TEACHING SIMPLE PRESENT TENSE BY USING CROSSWORD PUZZLE AT EIGHT GRADE OF SMPN 2 SUMBERGEMPOL - Rahmawati, Septina (Lingua Scientia, 2013)
Abstract: Education Unit Level Curriculum of SMPN 2 Sumbergempol (KTSP) states that learning English aims to develop studentsâ communicative competence in English orally and written. It refers to the competence of mastering grammar. The observation on studentsâ ability in mastering grammar before the research shows that students find difficulties to understand the function and the formula. The student from class C shows that their English ability especially in simple present is still low. The researcher got this data from the teacher note and observation list, given to the students before the researcher did this research. The researcher found some conclusions from the data, they are: 1) Studentsâ vocabularies is limited, 2) Studentsâ structure in making simple present is also bad, 3) students are still confused about the function and the formula of simple present. Based on the problem, the researcher intends to develop the strategy of encouraging students to understand simple present. This study is a Classroom Action Research. From all of the process in cycle 1 and II, the improvement of the studentsâ score from cycle I to cycle II was 62%. Based on the result, the studentsâ achievement after using crossword puzzle game is improved. By observing the studentsâ process in learning simple present from cycle 1 until cycle 2 there are some developments in the teaching and learning process. Reviewing at the result of the study, researcher concluded that an increase in the studentsâ ability on simple present had happened after being taught by crossword puzzle game.Keywords: Crossword Puzzle in Teaching Simple Present Tense